PERAN APLIKASI CANVA DALAM MENDUKUNG UMKM BERSAING DI ERA DIGITAL - Alamsyah, Andi Indra Saputra (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
This research analyzes the role of the Canva application in supporting Micro, Small, and Medium Enterprises (MSMEs) in the digital era. Using a qualitative research method through a case study approach involving two MSME players in Balikpapan City, the results show the positive impact of Canva on marketing and branding performance. The use of Canva as an e-Catalog, increased awareness, online sales, and enhanced competitiveness are acknowledged as significant positive outcomes. Although most informants have succeeded in improving design effectiveness, challenges related to understanding complex features and the intention of some informants to reduce or discontinue the use of Canva are identified. Continuous evaluation and improvement involve monitoring design trends, adopting new features, adjusting marketing strategies, and enhancing creativity. In conclusion, Canva has a positive impact on MSMEs, enabling them to compete in the digital realm. However, continuous efforts in evaluation, development, and training are needed to maximize the potential benefits of Canva for the growth and development of MSMEs in the digital world. By understanding the challenges and opportunities that arise, MSMEs can continue to optimize the use of Canva to achieve success and remain competitive in the ever-evolving digital era